O fenômeno da ansiedade além da patologização no contemporâneo: um olhar fenomenológico hermenêutico - QUEIROZ, Talita da Silva (2024)
Anxiety is widely discussed in various contexts in contemporary society, a time of intense transformations where the self-imposed pressure for personal and professional success, epitomized by the maxim of productivity, finds fertile ground. In this context, there is a special emphasis on the pathological expressions of anxious phenomena, as discussions are centered around their imbalances. This master's thesis investigates the phenomenon of anxiety beyond its pathological dimension, considering anxiety as a multifaceted human experience influenced by various social, economic, and personal factors. Through a qualitative study based on Martin Heidegger's hermeneutic phenomenological analytics, the research aimed to understand the meanings of anxiety in Brazilian Psychology over the last twenty years, using hermeneutic phenomenology as its methodology. The investigation included a bibliographic survey of scientific production in Psychology, the description and interpretation of the main understandings of anxiety, and the presentation of these understandings in conjunction with hermeneutic phenomenology to explore the phenomenon of anxiety in contemporary times. Additionally, an exploratory review in the first part of the investigation aimed to historically situate the concept of anxiety. The results highlighted a lack of qualitative studies on the phenomenon in question, revealing the need for a deeper understanding that considers individual experiences. Four categories of meaning were constructed: anxiety as a human experience; its relation to the possibility of premature death; its connection with situations of financial insecurity; and its association with social judgment. The research concluded that anxiety can be intensified in certain contexts, but there are also possibilities for harmonious coexistence with it. As final considerations, the study reinforces the importance of qualitative research to understand anxiety more holistically and suggests the need for future investigations into coping strategies and the role of public policies in supporting anxious experiences. It is hoped that the dissertation will contribute to the construction of a critical Clinical Psychology that respects the unique experiences of anxiety, promoting the naturalization of this phenomenon as an inherent part of the human existential experience.